2001
DOI: 10.1093/nar/29.8.1741
|View full text |Cite
|
Sign up to set email alerts
|

Sequences upstream of the branch site are required to form helix II between U2 and U6 snRNA in a trans-splicing reaction

Abstract: Three different base paired stems form between U2 and U6 snRNA over the course of the mRNA splicing reaction (helices I, II and III). One possible function of U2/U6 helix II is to facilitate subsequent U2/U6 helix I and III interactions, which participate directly in catalysis. Using an in vitro trans-splicing assay, we investigated the function of sequences located just upstream from the branch site (BS). We find that these upstream sequences are essential for stable binding of U2 to the branch region, and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 89 publications
1
24
0
Order By: Relevance
“…What may underlie this signal? Previous studies have indicated that initial binding of U2 snRNP to the BS region must be stabilized by an interaction with an anchoring site, located upstream of the BS (Gozani et al 1996;Kramer 1996;Ast et al 2001). Thus, this signal may serve as such an anchoring site.…”
Section: Splicing In Y Lipolyticamentioning
confidence: 99%
“…What may underlie this signal? Previous studies have indicated that initial binding of U2 snRNP to the BS region must be stabilized by an interaction with an anchoring site, located upstream of the BS (Gozani et al 1996;Kramer 1996;Ast et al 2001). Thus, this signal may serve as such an anchoring site.…”
Section: Splicing In Y Lipolyticamentioning
confidence: 99%
“…Another element in the upstream flank that may be distinct from an ISE is an anchoring site of 20 nt just upstream of the BP. This region has been implicated in sequence-independent binding of U2 snRNP proteins (Gozani et al 1996), but its role in splicing can be sequence dependent (Ast et al 2001). Finally, taking the extent of the polypyrimidine tract to be ‫41מ‬ is a bit arbitrary, as the overrepresentation of pyrimidines extends at a lower level beyond that distal limit (Penotti 1991;Stephens and Schneider 1992;.…”
mentioning
confidence: 99%
“…Next, the U4/U5/U6 trisnRNP complex is added, resulting in an apparent destabilization of U1 snRNP from the spliceosome (reviewed in reference 24), followed by several rearrangements in which U1 is replaced by U5 and U6 at the 5Јss (1,4,5,22,27,32). The U4/U6 base pairing within the U4/U5/U6 complex is disrupted, U4 is released from the spliceosome, and U6 snRNA base pairs with U2 snRNA (3,10,26,36,37,60). These rearrangements finally allow the two constitutive catalytic steps to generate mature mRNA and liberate the intron.…”
mentioning
confidence: 99%